Kitchen Sinks Have a History - Lucas, Fiona (Cuizine)

(untitled) (McGill University Library, 2012)
The kitchen sink, with its plentiful hot and cold running water, is a mundane feature of our daily lives that we take for granted—unless, that is, the water dries up or turns smelly, thereby inconveniencing our schedules or threatening our health, or unless we are considering a house purchase or renovation. The tap turns on, the water obligingly pours out; the tap turns off, the water obligingly drains away. Of course it was not always so. The advancement of kitchen sinks from dishpans filled with buckets of water to today’s carefully controlled municipal system—with its in/out pipes, hot water tanks, and on/off taps—reflects developments in plumbing technology, society’s evolving concerns about civic and moral health, and major alterations in expectations around women’s work. Although lavatory and laundry sinks were equally transformative, the focus of this paper is the kitchen sink, and the irksome daily cycle of dishwashing in Ontario homes of the 19th and 20th centuries.